National Model: An approach to comprehensive eye examinations for children entering the school system - ACO, CAO (Canadian Journal of Optometry, 2021)
In February 2005, the Children's Vision Initiative (CVI) of the Canadian Association of Optometrists (CAO) submitted a project funding application to the Community Development and Partnerships Directorate of Social Development Canada. While the submission did not ultimately meet the requirements for funding, the application process proved to be a beneficial exercise in clearly articulating CAO's approach for comprehensive eye examinations for children entering the school system. CVI may also use the material to apply to other government programs.